Penyuluhan Antibiotik Sebagai Pencegahan Resistensi pada Pasien Rawat Jalan di Rumah Sakit - Nurhidayati Harun; Nia Kurniasih; Marlina Indriastuti; Susan Sintia Ramdhani; Annis Rahmawaty; Putri Salsabila Haerunisa; Rina Nurmaulawati (Yayasan REDI Tiga Monas, 2024)
The improper use of antibiotics is a major cause of antimicrobial resistance, a serious global health issue. Resistance occurs when bacteria become immune to drugs, making infections harder to treat. One of the main causes is a lack of public understanding regarding how to obtain, use, store, and dispose of antibiotics properly. Outpatients are particularly at risk as they often manage antibiotics independently at home, such as obtaining them without a prescription, stopping treatment prematurely, or saving leftover medication for future use without consulting a doctor. This educational session aimed to inform outpatients on proper antibiotic management to reduce resistance. Activities were conducted through interactive presentations and discussions at Pandega Hospital's outpatient department in Pangandaran. The results showed positive responses and enthusiasm from participants, who actively asked questions and engaged in discussions. Patients gained a clear understanding of the DAGUSIBU Antibiotics concept, including obtaining antibiotics with a prescription, using them as directed, storing them safely, and disposing of unused medication responsibly. This session successfully improved patients’ knowledge and awareness about proper antibiotic management, representing an essential step in preventing antimicrobial resistance. Its success can serve as a model for similar programs in other areas, supporting safer and more responsible antibiotic use.